Nitrogen Supply and Host-Plant Genotype Modulate the Transcriptomic Profile of Plasmodiophora brassicae - Gazengel, Kévin; Aigu, Yoann; Lariagon, Christine; Humeau, Mathilde; Gravot, Antoine; Manzanares-Dauleux, Maria J.; Daval, Stéphanie (Frontiers in Microbiology, 2021)
Nitrogen fertilization can affect the susceptibility of Brassica napus to the telluric pathogen Plasmodiophora brassicae. Our previous works highlighted that influence of nitrogen can strongly vary regarding plant cultivar / pathogen strain combinations, but underlying mechanisms are unknown. The present work aims to explore how nitrogen supply can affect the molecular physiology of P. brassicae through its life epidemiological cycle. A time-course transcriptome experiment was conducted to study the interaction, under two conditions of nitrogen supply, between isolate eH and two B. napus genotypes (Yudal and HD-018), harboring (or not harboring) low nitrogen-conditional resistance toward this isolate (respectively). P. brassicae transcriptional patterns were modulated by nitrogen supply, these modulations being dependent on both host-plant genotype and kinetic time. Functional analysis allowed the identification of P. brassicae genes expressed during the secondary phase of infection, which may play a role in the reduction of Yudal disease symptoms in low-nitrogen conditions. Candidate genes included pathogenicity-related genes (‘NUDIX’, ‘carboxypeptidase’ and ‘NEP-proteins’) and genes associated to obligate biotrophic functions of P. brassicae. This work illustrates the importance of considering pathogen's physiological responses to get a better understanding of the influence of abiotic factors on clubroot resistance/susceptibility.